PENGARUH KONSENTRASI DAN LAMA PERENDAMAN ZPT AUKSIN DALAM MEMPERCEPAT PERTUMBUHAN TUNAS BULBIL PORANG (Amorphophallus muelleri Blume) - Qurrota Ayun Fahra Hasanah; Darso Sugiono; Yayu Sri Rahayu (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2023)
The use of growth regulators before planting porang is one way to increase the growth of porang bulbils. The research was conducted with the aim of getting the length of immersion that gives the best effect on each concentration of auxin ZPT in accelerating the growth of bulbil porang (Amorphophallus muelleri Blume) shoots.. The research method used is experimental method using factorial Randomized Group Design (RBD) 4x4, which consists of 16 treatments and repeated 2 times. The first factor is concentration which consists of 4 levels, namely k0 (control), k1 (200mg/l), k2 (300mg/l), and k3 (300mg/l). The second factor is immersion time which consists of 4 levels, namely l1 (60 minutes), l2 (120 minutes), l3 (180 minutes), and l4 (240 minutes). There is an interactiont between concentration and immersion time on sprouting time, vigor index, and diameter of bulbil porang shoots at 42 and 56 days after planting. The concentration of 200mg/l (k1) at a immersion time of 180 minutes (l3) gave the fastest sprouting time of 15.2 days. The concentration of 200mg/l (k1) at 180 minutes immersion time (l3) gave the highest vigor index value of 100%. The length of immersion l4 (240 minutes) at the growth regulator concentration k1 (200mg/l) gave the best bulbil porang shoots diameter of 2.96 mm.